A Knowledge Translation framework on ageing and health. Issue 3 (March 2017) - Ellen, Moriah E.; Panisset, Ulysses; Araujo de Carvalho, Islene; Goodwin, James; Beard, John
Highlights: The need to ensure that research into older peoples' health is translated to policy is immediate. A framework to enable evidence-informed policy making in ageing and health is proposed. The framework consists of seven elements that include researcher and stakeholder initiatives. A four-step process for implementation of the framework is proposed. Abstract: Background: The world's population aged 60 and over will more than triple from 600 million to 2 billion between the years 2000 to 2050. This demographic change has significant impact on health, social, and economic sectors. The need to ensure that research into older peoples' health is effectively translated to policy is immediate. Objective: The purpose of this paper is to present a proposed framework to support evidence informed policymaking in ageing and health. Methods: We undertook a two stage process to develop the framework. We (a) conducted a review of the literature, and (b) convened an expert panel to provide feedback. Results: Numerous frameworks have been proposed yet the majority do not address all the barriers. The Lavis et al., framework addresses a majority of the obstacles associated with evidence-informed policymaking and this framework was modified to include sub-elements important to ageing and health and to reflect the order of importance of the elements. The main elements are: a climate and/or context for research use, linkage and exchange efforts, creation of new knowledge, push efforts, facilitating pull efforts, pull efforts, and evaluation. A four-step implementation process is proposed. Discussion: This paper offers an approach to Knowledge Translation within the field of ageing and health. The framework and proposed implementation could be used to conceptualize and implement evidence-informed policymaking.